Master Z [videorecording (DVD)] : Ip Man legacy - Yuen, Wo-ping, 1945-; Zhang, Jin, 1974 May-; Bautista, David, 1969-; Bautista, David, 1969-; Yeoh, Michelle, 1963- (Well Go USA Entertainment, 2019)
After his defeat at the hands of Ip Man, Cheung Tin Chi leaves martial arts behind and starts waiting tables, but his skills soon draw him into a fight with a drug lord.